2012
DOI: 10.3390/en5051433
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Mutual Effect among Nearby Needles in a Multi-Needle Configuration of an Atmospheric Air Dielectric Barrier Discharge

Abstract: Abstract:A numerical study has been conducted to understand the mutual effect among nearby needles in a multi-needle electrode dielectric barrier discharge. In the present paper, a fluid-hydrodynamic model is adopted. In this model, the mutual effect among nearby needles in a multi-needle configuration of an atmospheric air dielectric barrier discharge are investigated using a fluid-hydrodynamic model including the continuity equations for electrons and positive and negative ions coupled with Poisson's equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Moreover, they showed that increasing the length of the reactor can increase the removal efficiency of NO. In 2011 and 2012, Wang et al [13,17] studied a Multineedle-to-Cylinder Configuration of DBD reactor experimentally and numerically and investigated the effect of needles arrayed structure and needle arrangement on the inner electrode. They showed that by using the Multineedle-to-Cylinder system, higher performance of DBD reactor can be achieved compared to the regular DBD reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they showed that increasing the length of the reactor can increase the removal efficiency of NO. In 2011 and 2012, Wang et al [13,17] studied a Multineedle-to-Cylinder Configuration of DBD reactor experimentally and numerically and investigated the effect of needles arrayed structure and needle arrangement on the inner electrode. They showed that by using the Multineedle-to-Cylinder system, higher performance of DBD reactor can be achieved compared to the regular DBD reactor.…”
Section: Introductionmentioning
confidence: 99%
“…The VDBD reactor was widely used for the treatment of NO X and SO X . The structure parameters of DBD reactor have great impact on NO removal efficiency and energy consumption, which has become a research hotspot [14][15][16][17][18][19]. For SOX removal, wet scrubbing can achieve a higher removal efficiency (more than 95%), while, for NOX removal, wet scrubbing has a low removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The VDBD reactor was widely used for the treatment of NOX and SOX. The structure parameters of DBD reactor have great impact on NO removal efficiency and energy consumption, which has become a research hotspot [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1980s, Morrow was the first to calculate the streamer propagation and the distributions of charged particles based on Possion's equation and continuity equations [32,33]. Afterwards, several scholars worked out many new methods to solve the Possion's equation and continuity equations, therefore, the streamer discharge of different kinds of electrodes was computed [19,[34][35][36][37][38][39][40][41], at the same time, the characteristics of streamer pulses in corona discharges were also measured [17][18][42][43][44][45]. However, little attention has been paid to the variation of charged particles density and development of streamer during corona discharge.…”
Section: Introductionmentioning
confidence: 99%